“Well-known” as in well-known trade marks : the scope of well-known marks protection in South Africa and other jurisdictions - Okorie, Chijioke (University of Pretoria, 2025)
Mini Dissertation (LLM (Intellectual Property))--University of Pretoria, 2024.